PELAKSANAAN MANAJEMEN KEUANGAN DALAM RANGKA MENINGKATKAN EFEKTIVITAS PENGGUNAAN ANGGARAN DI JENJANG PENDIDIKAN DASAR YAYASAN PENDIDIKAN CENDANA RIAU - SILVIA NORA; ALMASDI SYAHZA; ZULFAN SAAM (Universitas Riau, 2017)
This research aims to describe and analyse the implementation of the financialmanagement in order to improve the effectiveness of budgetusing in basic level of educationatYayasan Pendidikan Cendana Riau.This research uses descriptively qualitative approach method.In this study a sample chosen purposive with a total of 11 participants or interviewers.Datacollection was done through observation, interview and documentation.Data analysis is donethrough a process of data reduction, data display, and drawing conclusion/verification. Thevalidity of data is tested through a test of credibility, dependability, and confirmability test.Theresult of this research is the implementation of financial management in order to improve theeffectiveness of budget using inbasic level of educationat Yayasan Pendidikan Cendana Riau.That has been done well because management functions are already done properly as well aspertaining the planning and preparation of the budget, organizing, direction, control, andsupervision of financial resources, Thus the Division of authority and a clear responsibility inthe system of management and organization, the existence of adequate accounting systems,theexistence of evaluation and analysis for assessing organizational performance, as well as supportfrom implementers starting from the top level to the bottom so that the achievement of theeffectiveness in the use of budget in basic level of educationat Yayasan Pendidikan CendanaRiau can be reached.